The Epidermis in Microgravity and Unloading Conditions and Their Effects on Wound Healing - Bacci, Stefano; Bani, Daniele (Frontiers in Bioengineering and Biotechnology, 2022)
The future objectives of human space flight are changing from low-term permanence in the International Space Station to missions beyond low Earth orbit to explore other Planets. This implies that astronauts would remain exposed for long time to a micro-gravity environment with limited medical support available. This has sparkled medical research to investigate how tissues may adapt to such conditions and how wound repair may be influenced. This mini-review will be focused on the effects of microgravity and unloading conditions on the epidermis and its keratinocytes. Previous studies, originally aimed at improving the in vitro protocols to generate skin substitutes for plastic surgery purposes, showed that epidermal stem cells cultured in simulated microgravity conditions underwent enhanced proliferation and viability and reduced terminal differentiation than under normal gravity. In the meantime, microgravity also triggered epithelial-mesenchymal transition (of keratinocytes, promoting a migratory behavior. The molecular mechanisms of such deep influences on keratinocyte growth and differentiation involve mechano-transduction signals and pathways whereby specific target genes are activated, i.e. those presiding to circadian rhythms, migration and immune suppression, or inhibited, i.e. those involved in stress responses. However, although these in vitro studies appeared to suggest that microgravity would accelerate wound healing, in vivo evidence on animals exposed to low gravity rather suggest that prolonged mechanical unloading contributes to delayed, aberrant epidermal repair. This apparent paradox can be explained by the complex interplay of regulatory signals exchanged between the epidermis and dermis in the skin as a whole, which undoubtedly deserve further investigation.